Learning to teach art and design in the secondary school a companion to school experience - Addison, Nicholas 1954-; Burgess, Lesley 1952- (London Routledge, 2015)
"Learning to Teach Art and Design in the Secondary School explores a range of approaches to teaching and learning and provides a conceptual and practical framework for understanding the diverse nature of art and design in the secondary school curriculum.
Includes bibliographical references and index.
Keywords: Art -- Study and teaching (Secondary) -- Great Britain